THE RELATIONSHIP OF HOSPITALITY AND PATIENT’S SATISFACTION IN VANDA AND EDELWEIS ROOM AT REGIONAL PUBLIC HOSPITAL BOGOR: HUBUNGAN FASILITAS RUANG RAWAT INAP DENGAN KEPUASAN PASIEN DI RUANG VANDA DAN EDELWEIS RSUD KOTA BOGOR - Mulyani Siti Mulyani (Jurnal Ilmiah Wijaya, 2019)
Facilities are the important factor to determine patient satisfaction. The completeness of facilities also determine the assessment of patient satisfaction, such as health facilities both facilities and infrastructure, parking lots, comfortable waiting room and inpatient room space. To choose a product especially the product of service, where the completeness and adequacy of facitilies given will make consumer (patient) feel satisfied with the product which is used. The purpose is to know the correlation between the inpaient room facility and patient satisfaction and to identify distribution frequency of the facilities in inpatient room Vanda and Edelweis at Regional Public Hospital Bogor. This research uses Descriptive Quantitative Analytic with Cross Sectional research design. The method of sampling which used in this research is Random Sampling with the number of samples of 164 respondents which used by patient medical record. The instruments which used are questionnaire, while the data analysis technique which used are univariate and bivariate analysis by using Chi-Square statistical test. From 164 respondents with the inappropriate facilities that 104 respondents reached (63.4%), while patients were not satisfied with the existing facilities in Vanda and Edelweiss inpatient room at Regional Public Hospital Bogor, then 96 respondents (58.5%) while the facilities which did not suitable and the patients whom were dissatisfied are 68 respondents (41.5%). The result of statistical test using Chi-Square test obtained p value 0,029 (p <0,05) and value of OR 2,159. The conclusion of this research is, there are the relationship between the inpatient room facilities and patient satisfaction in vanda and edelweis room in Regional Public Hospital Bogor. Accordig to the research, the researcher recommends that is really expected this present research can give some inputs for Bogor government, especially for Regional Public Hospital of Bogor can Improving the quality of inpatient room facilities which are provided.